Evaluation of the impact of statin therapy on the obesity paradox in patients with acute myocardial infarction: A propensity score matching analysis from the Korea Acute Myocardial Infarction Registry. Issue 35 (September 2017) - Won, Ki-Bum; Hur, Seung-Ho; Nam, Chang-Wook; Ann, Soe Hee; Park, Gyung-Min; Lee, Sang-Gon; Kim, Hyo-Eun; Cho, Yun-Kyeong; Yoon, Hyuck-Jun; Park, Hyoung-Seob; Kim, Hyungseop; Han, Seongwook; et al.
Abstract : Abstract: The phenomenon of obesity paradox after acute myocardial infarction (AMI) has been reported under strong recommendation of statin therapy. However, the impact of statin therapy on this paradox has not been investigated. This study investigated the impact of statin therapy on 1-year mortality according to obesity after AMI. A total of 2745 AMI patients were included from the Korea Acute Myocardial Infarction Registry after 1:4 propensity score matching analysis (n = 549 for nonstatin group and n = 2196 for statin group). Primary and secondary outcomes were all-cause and cardiac death, respectively. During 1-year follow-up, the incidence of all-cause (8.4% vs 3.7%) and cardiac (6.2% vs 2.3%) death was higher in nonstatin group than in statin ( P  < .001, respectively). In nonstatin group, the incidence of all-cause (7.2% vs 9.0%) and cardiac (5.5% vs 6.5%) death did not differ significantly between obese and nonobese patients. However, in statin group, obese patients had lower 1-year rate of all-cause (1.7% vs 4.8%) and cardiac (1.2% vs 2.9%) death ( P  < .05, respectively), and lower cumulative rates by Kaplan–Meier analysis of all-cause and cardiac death compared with nonobese patients (log-rank P  < .05, respectively). The overall risk of all-cause death was significantly lower in obese than in nonobese patients only in statin group (hazard ratio: 0.35; P  = .001). After adjusting for confounding factors, obesity was independently associated with decreased risk of all-cause death in statin group. In conclusion, the greater benefit of statin therapy for survival in obese patients is further confirmation of the obesity paradox after AMI. Abstract : Supplemental Digital Content is available in the text